Invader probes: harnessing the energy of intercalation to facilitate recognition of chromosomal DNA for diagnostic applications1. Issue 8 (14th August 2015) - Guenther, Dale C.; Anderson, Grace H.; Karmakar, Saswata; Anderson, Brooke A.; Didion, Bradley A.; Guo, Wei; Verstegen, John P.; Hrdlicka, Patrick J.
<x xml:space="preserve">Abstract</x> Optimized Invader probes enable efficient (C50 < 1 μM), fast (t50 < 3 h), kinetically stable (>24 h), and single nucleotide specific recognition of DNA targets.